Olhares sobre os educadores de adultos no processo de reconhecimento de competências: o caso dos profissionais de RVC - Isabel Fonseca Paulos, Catarina (Revista Vozes dos Vales: Publicações Acadêmicas, 2014)
The article draws an initial perspective about the professional activity of the RVC professionals, adult educators involved in the competence recognition, validation and certification process. It is based on the results of an exploratory study, focused on semi-structured and biographical interviews done with RVC professionals. This research focused principally on the following questions: Who are the RVC professionals? What are their previous professional experiences? Which identitary forms they developed during their work as RVC professionals? How did they learn to do all tasks involved? What image do they have of themselves? What meanings have they attributed to themselves and to their work? What projects do they have for their future? These adult educators have a self-image mainly centered on the relationship component of their professional activity.